Difficulties in evaluating on-farm experiments with livestock: Examples from the Ethiopian highlands - Gryseels, Guido (International Livestock Centre for Africa, 1986)
Discusses the on-farm trials with crossbred cows conducted in the highlands of Ethiopia (Debre Zeit/Debre Berhan) to study productivity under farm conditions, to appraise smallholder adoption problems and to evaluate the impact on the socio-economic welfare of the farmer and his family; summarizes also the difficulties in conducting and evaluating on-farm livestock research.